Modern cosmology - Dodelson, Scott; Schmidt, Fabian; Schmidt, Fabian (London: Academic Press, 2021)
Modern Cosmology, Second Edition, provides a detailed introduction to the field of cosmology. Beginning with the smooth, homogeneous universe described by a Friedmann-Lemaître-Robertson-Walker metric, this trusted resource includes careful treatments of dark energy, big bang nucleosynthesis, recombination, and dark matter. The reader is then introduced to perturbations about an FLRW universe: their evolution with the Einstein-Boltzmann equations, their primordial generation by inflation, and their observational consequences: the acoustic peaks in the CMB; the E/B decomposition in polarization; gravitational lensing of the CMB and large-scale structure; and the BAO standard ruler and redshift-space distortions in galaxy clustering. The Second Edition now also covers nonlinear structure formation including perturbation theory and simulations. The book concludes with a substantially updated chapter on data analysis. Modern Cosmology, Second Edition, shows how modern observations are rapidly revolutionizing our picture of the universe, and supplies readers with all the tools needed to work in cosmology.--
The concordance model of cosmology -- The expanding universe -- The fundamental equations of cosmology -- The origin of species -- The inhomogeneous universe : matter & radiation -- The inhomogeneous universe : gravity -- Initial conditions -- Growth of structure : linear theory -- The cosmic microwave background -- The polarized CMB -- Probes of structure : tracers -- Growth of structure : beyond linear theory -- Probes of structure : lensing -- Analysis and inference.
Previous edition: 2003
Keywords: Cosmology; Cosmology